Safety and efficacy of herbal tea for patients with diabetes mellitus - Abdullah, Siti Syarihan; Alkhoshaiban, Ali Saleh; Mani, Vasudevan; Akkawi, Muhammad Eid; Ming, Long Chiau (Wolters Kluwer - Medknow, 2016)
Purpose: The aim of this report is to review (i) safety and efficacy and (ii) medical marketing and regulation of Glucos Cut (GC) Tea. Methodology: The electronic databases such as PubMed, ScienceDirect, Google Scholar, and MEDLINE via EBSCOhost were searched with no limit to year of publication. Additional information was obtained from the Micromedex, 1CMedicines (Advertisement and Sales) Act 1956 1D and the 1CGuideline on Advertising of Medicines and Medicinal Products to General Public 2006. 1D Results: Of total 28 articles reviewed, only 20 relevant full 11text articles were obtained and reviewed. GC Tea consists of five different herbs, i.e. green tea, Gymnema sylvestre, mulberry leaf, rooibos tea, and stevia. Green tea, mulberry leaf, and rooibos tea were reported to be effective at improving lipid profile and also exhibit a good antioxidant property. Review also found that G. sylvestre has a sweet suppression activity while stevia showed a significant reduction in postprandial glucose. All these five herbs were reported to have minimal adverse effect, which make it safe for human consumption. GC Tea is categorized as a drinking supplement, which is controlled by the Food Safety and Quality Division, Ministry of Health. Hence, it does not need to be registered with the National Pharmaceutical Control Bureau. Conclusion: GC Tea has benefits in reducing risk of diabetes, cardiovascular diseases, and obesity. GC Tea also has antioxidant properties that help reduce risk of cancer. Only mild adverse effects were reported when consuming these herbs in recommended dose.